Dampak Knowledge Management Terhadap Kinerja Karyawan: Sebuah Pendekatan Manajemen Islam - Salihah Khairawati; Nimas Arganingtyas; Hery Sasono; Wijiharta Wijiharta (ITB AAS INDONESIA Surakarta, 2021)
This research aims to test the influence of knowledge management consisting of three dimensions (person, procedure and technology) on employee performance. The method used in this study is a mixed method with an explanatory sequential design that combines quantitative research methods with qualitative sequentially, where in the first stage use quantitative and second stage methods with qualitative methods. With this method is expected to be obtained deeper research findings. The study respondents were 35 people wich all of them are employee. Analyze data using SPSS software version 25 with non parametric test. Non-parametric tests are performed because the data is not distributed normally. The results of the study prove that personnel affect employee kierja, job procedure concerns employee performance and technology affects employee performance. All dimensions of knowledge management demonstrate its influence on employee performance. The position of knowledge in Islam is very important, on the basis that the company also makes knowledge as an aspect that gets great attention. The company's policies and strategies are driven by the motivation of implementing Islamic values and practising knowledge